2018
DOI: 10.1016/j.ssci.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial and proactive “safety citizenship behaviour” (SCB): The mediating role of affective commitment and psychological ownership

Abstract: Safety citizenship behaviour (SCB) is an important participation factor in work-groups. Our study aims to study the influence of some antecedents of this safety-specific dimension of organizational citizenship. In the light of the current research stream that distinguishes between prosocial vs. proactive forms of organizational citizenship, we will investigate the effects of the following variables: organizational support for safety participation; team safety climate; psychological ownership toward the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 51 publications
6
96
0
1
Order By: Relevance
“…Similarly, a recent study by Curcuruto & Griffin (2018) on safety citizenship behaviours (SCBs) showed that psychological ownership predicted a change-oriented typology of SCB like safety voice, whereas affective commitment affected an affiliative oriented form of SCB like stewardship. The authors suggested that, in the same way that task performance and citizenship can be considered as having more or less proactive forms, SCBs can also be more or less proactive, and be directed both to other people and to the organization itself.…”
Section: Initiating a Safety Related Change: A Distinct Form Of Safetmentioning
confidence: 91%
See 4 more Smart Citations
“…Similarly, a recent study by Curcuruto & Griffin (2018) on safety citizenship behaviours (SCBs) showed that psychological ownership predicted a change-oriented typology of SCB like safety voice, whereas affective commitment affected an affiliative oriented form of SCB like stewardship. The authors suggested that, in the same way that task performance and citizenship can be considered as having more or less proactive forms, SCBs can also be more or less proactive, and be directed both to other people and to the organization itself.…”
Section: Initiating a Safety Related Change: A Distinct Form Of Safetmentioning
confidence: 91%
“…Specifically, we predict that self-reported safety compliance will predict external ratings of employees' engagement in legally mandated reporting of risks, hazards, property damages, omission and violations. We also suggest that affiliative forms of safety citizenship behaviour (SCB) -like safety helping -are intrinsically aimed both at protecting other people and at supporting the standard organizational effectiveness Curcuruto & Griffin, 2018). Therefore, we expect that self-reported safety helping will be associated with employees' engagement in prescribed reporting as mandatory by safety regulation systems.…”
Section: Organizational Outcomes Of Safety Initiativementioning
confidence: 99%
See 3 more Smart Citations